Phage mediated growth inhibition and biofilm disruption of the endodontic pathogen Enterococcus faecalis - Daniel K. Arens; Meili Jensen; Meaghan A. Rose; Heather M. Zamora; Eun Y. Huh; Yoon Y. Hwang (PLoS ONE, 2026)
The failure of endodontic procedures such as root canal therapy is primarily indicated by persistent microbial infections. Root canal therapy involves the removal of decaying dental pulp (internal blood vessels and nerves of teeth), sanitizing the canal, and filling the space with biocompatible materials. Improper cleaning or the breakdown of these materials can lead to secondary infections. These infections, if left untreated, can lead to severe pain, bone and tooth loss, and potentially systemic infection. The bacterium Enterococcus faecalis is one of the most commonly associated organisms with failed root canal therapy, in addition to its prevalence in urinary tract infections, endocarditis, wounds, and sepsis. E. faecalis is known to survive in low nutrient environments and produce extensive biofilms, making it difficult to eradicate. In addition to antibiotic treatment, bacteriophages (phages), which are bacteria-specific viruses that kill their host are an interesting companion or alternative to antibiotics. In this study we isolated and characterized 14 E. faecalis phages from wastewater samples by testing their host range, growth inhibition, and biofilm eradication capabilities against several E. faecalis strains including two that were orally derived. Several phages showed broad host ranges (up to 16 strains), strong bacterial growth inhibition even when applied at low concentrations, and significant eradication of mature biofilms (97% reduction). The phages presented here represent a unique repertoire of antibacterial agents for use in treating endodontic infections and add to the growing library of E. faecalis phages to treat diverse infections.